Critical analysis of interprofessional student-led community health promotion workshops - Catherine O'Connor; Alyssa Labelle; Tyler Pretty; Kayla Katerynuk; Gayle Adams-Carpino (Rural and Remote Health, 2025)
Introduction: Health promotion interventions can empower communities and individuals by focusing on social and environmental interventions, rather than on individual behaviour changes. The settings-based approach, rooted in WHO's Health for All initiative, emphasizes community involvement, collaboration, and equity. Community-based health promotion, especially in rural and remote areas where there is a higher proportion of underserved populations, can leverage community assets and promote health equity. Student-led health promotion initiatives are gaining traction, benefiting both students and communities. Reach Accès Zhibbi (RAZ), a student-led organization in Sudbury, Ontario in Canada delivers evidence-based health promotion workshops to vulnerable populations, promoting health literacy and equity. This study examines the impact of RAZ's workshops, addressing a gap in research on student-led, non-clinical health promotion efforts. Methods: This cross-sectional mixed-methods study examined RAZ workshops at five partnering community agencies. Data was collected with two surveys: a web-based survey for staff and a paper-based survey for workshop participants. The first gathered perspectives on long-term impacts of the workshops, while participant surveys were given before and after the workshops to assess baseline knowledge, learning, and behavioural intent. The surveys were developed using the Health Behaviour Scale-16 and were designed at a grade 5 reading level for accessibility. Data analysis involved frequency analysis and Wilcoxon signed-rank test to assess perceived learning gains. Thematic analysis was conducted on qualitative data. Results: Seven employees from three of the five partnering agencies rated the effectiveness of RAZ workshops, with a mean score of 9 out of 10. They highlighted benefits such as increased knowledge, skills, and mental wellness. Thematic analysis identified three key themes: long-term impact, practical application, and mutual collaboration. Among 33 workshop participants, significant improvements were observed in health literacy, decision-making, and physical and mental health knowledge post-workshop. A Wilcoxon signed-rank test on adjusted change scores for pre- and post-workshop data revealed statistically significant gains in perceived learning across all aspects. Most attendees found the workshop helpful, with 57.6% planning behaviour changes. Conclusion: This study showed that interprofessional student-led health promotion workshops effectively enhance health literacy and empower underserved communities. Significant improvements in participants' knowledge and confidence suggest these workshops help address health disparities. The findings highlight their potential scalability and adaptability across communities, promoting sustainable health promotion efforts, an important consideration for rural and remote communities.